Fair Trial in Mothers of Srebrenica et al.: Guessing as a Form of Reasoning - Ratniece, Zane (Utrecht Journal of International and European Law, 2021)
On 19 July 2019, the Dutch Supreme Court (Hoge Raad) rendered the final judgment in the proceedings led by Stichting Mothers of Srebrenica (‘Mothers’), a foundation established under the Dutch law, in the interests of more than 6,000 surviving relatives of the Srebrenica genocide. Mothers and ten individual plaintiffs alleged multiple failures by the Dutch State regarding the fall of the Srebrenica safe area designated by the United Nations (‘UN’) and the fate of more than 30,000 people who had fled to either a nearby compound of the Dutch battalion or other locations, including about 7,000 Bosniac males. However, the Supreme Court established the State’s responsibility only regarding a group of approximately 350 males who had been allowed inside the Dutchbat compound but were then handed over to the Bosnian Serbs. This contribution examines from the perspective of the right to fair trial how the courts determined the State’s liability for damages in relation to these males. It questions whether the parties to the proceedings had an opportunity to present their arguments on facts and evidence as to a percentage of the State’s liability for damages. It also views the Supreme Court’s determination of the liability at 10% as problematic.